MANAGING PREMARITAL GUIDANCE THROUGH A PSYCHOSOCIAL DA’WAH APPROACH: EVIDENCE FROM KUA SUNGGAL DISTRICT - Wadinil Haqq; Mohd Iqbal Abdul Muin (Hikmah: Journal of Islamic Studies, 2026)
AbstractThis study aims to analyze the management of premarital guidance based on a psychosocial da’wah approach at the Office of Religious Affairs (KUA) of Sunggal District. The study focuses on program planning and implementation, da’wah strategies for strengthening the psychosocial readiness of prospective couples, and the evaluation of the guidance program. This research employed a qualitative approach with a case study design. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed using an interactive analysis model. The findings indicate that premarital guidance at KUA Sunggal District was implemented in a structured manner by integrating Islamic da’wah values with psychosocial concerns. The da’wah strategies applied were communicative, persuasive, and dialogical through discussions, question-and-answer sessions, and case-based reflection, which contributed positively to the development of prospective couples’ mental, emotional, social, and spiritual readiness. Evaluation was conducted through reflection during the activities and follow-up consultations; however, it was not yet supported by a systematic long-term monitoring mechanism. This study concludes that premarital guidance based on a psychosocial da’wah approach can strengthen prospective couples’ readiness for married life, although it still requires improvement in sustainable evaluation systems and post-marital guidance. ABSTRAKPenelitian ini bertujuan untuk menganalisis manajemen bimbingan pranikah berbasis pendekatan dakwah psikososial di Kantor Urusan Agama (KUA) Kecamatan Sunggal. Fokus penelitian meliputi perencanaan dan pelaksanaan program, strategi dakwah dalam memperkuat kesiapan psikososial calon pasangan, serta evaluasi program bimbingan pranikah. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui observasi, wawancara semi-terstruktur, dan dokumentasi, kemudian dianalisis menggunakan model analisis interaktif. Temuan penelitian menunjukkan bahwa bimbingan pranikah di KUA Kecamatan Sunggal dilaksanakan secara terstruktur dengan mengintegrasikan nilai-nilai dakwah Islam dan perhatian terhadap aspek psikososial. Strategi dakwah yang diterapkan bersifat komunikatif, persuasif, dan dialogis melalui diskusi, tanya jawab, dan refleksi berbasis kasus, yang berkontribusi positif terhadap pengembangan kesiapan mental, emosional, sosial, dan spiritual calon pasangan. Evaluasi dilakukan melalui refleksi selama kegiatan dan konsultasi lanjutan; namun, evaluasi tersebut belum didukung oleh mekanisme pemantauan jangka panjang yang sistematis. Penelitian ini menyimpulkan bahwa bimbingan pranikah berbasis pendekatan dakwah psikososial dapat memperkuat kesiapan calon pasangan dalam memasuki kehidupan pernikahan, meskipun masih memerlukan penguatan pada sistem evaluasi berkelanjutan dan bimbingan pascanikah.